Commanding with compassion: harnessing the potential of military chaplains within the NATO structure - Grimell, Jan; Letovaltseva, Tatiana; Aalto, Janne; De Ceuster, Hans (Frontiers in Psychiatry, 2025)
The purpose of this article is to foster a better general understanding of military chaplains within NATO by elucidating their roles, highlighting what distinguishes military chaplains from military medical (psychiatrists and psychologists), and offering general suggestions on how military commanders at the tactical (battalion) level can benefit from military chaplains. The context for this paper is the ongoing research conducted by NATO’s Science and Technology Organization (STO) Human Factors and Medicine (HFM) Research Task Group (RTG) 352, titled “Moral Challenges in the Future Security Environment (FSE): Guidance for Leaders”, which began in 2022 and will continue through 2025. The research methodology employed in this article is known as collaborative inquiry, which emphasizes a partnership between academic researchers in military chaplaincy and practitioners (i.e. military chaplains) with the aim of bridging the gap between theory and practice. The following three questions have guided the collaborative methodology: What do military chaplains typically do when supporting service members? What concepts are used to describe their work? What distinguishes military chaplains from medical professionals? The results are presented in the article and describe, among other things, that despite significant variations among NATO members’ military chaplaincy services, chaplains generally exercise a ministry of presence. They are trained to address a wide range of spiritual, religious, moral, ethical and existential issues among service members and veterans. Additionally, non-clinical concepts related to moral injury (not yet a clinical diagnosis), such as guilt, shame, forgiveness, reconciliation, fall within the expertise of chaplains. Chaplains’ commitment to professional secrecy and confidentiality – considered absolute by some chaplains – as well as the ethical distance (from the command structure) provides a safe space for military personnel and veterans to express their feelings, thoughts, and experiences. Additionally, military chaplains are often experts in dealing with death and grief, enabling them to conduct ritually and morally dignified farewells for fallen soldiers and provide support to their comrades and units. These are just some examples of the areas of expertise that military chaplains typically master.